Investigating Influence of Arabic Teachers’ Pedagogical Skills on Students’ Engagement in Learning Arabic at Fatimah Azzahra Islamic Junior High School - Rikzan Hafif; Munirul Abidin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article aims to explore and understand the relationship between Arabic teachers' pedagogical competence and students' interest in learning Arabic among seventh grade students at Fatimah Azzahra Magelang Islamic Junior High School. This research is expected to provide in-depth insight into how the quality of Arabic teachers' teaching can affect students' interest and engagement in the learning process. This study used a correlational quantitative approach with data collection tools in the form of a questionnaire consisting of 16 questions for each variable. The research population was all seventh grade students totaling 66 people and at the same time served as the research sample. Data analysis was carried out using the Pearson correlation test. The results showed that there were 16 indicators on each variable (X and Y), with a normal distribution value of Asymp. Sig. 0.222 which indicates that the data is normally distributed. The linearity test produces a significance value of 0.033 which means that the data has a linear relationship. While the Pearson correlation test shows a significant value of 0.021 and a correlation coefficient value of 0.263. This indicates a weak but statistically significant relationship between Arabic teachers' pedagogical competence and students' interest in learning Arabic.